The Chemical Composition, In Vitro, In Vivo, and In Silico Studies of Extract of the Pelargonium graveolens plant found in the Eloued region - Ben Ali Fatma Zahra; Bousbia Salah Sadjida; Selatna Lina (جامعة الوادي university of eloued, 2026)
Pelargonium graveolensis a medicinal plant with notable pharmacological potential. This study evaluates the antidiabetic, antioxidant, anti-inflammatory, antimicrobial, and organprotective activities of its methanolic leaf extract using experimental and computational approaches. The extraction yield was 15.576%, and LC–MS analysis revealed a rich profile of bioactive compounds including rutin, quercetin derivatives, luteolin, curcumin, and phenolic acids. The extract exhibited strong antioxidant activity (DPPH and FRAP), significant α- amylase inhibition (>80%), and notable anti-inflammatory effects, while showing acceptable hemocompatibility at lower concentrations. Moderate antibacterial activity was observed against E. coli and S. aureus. In vivo studies demonstrated significant reductions in blood glucose and HbA1c, improved liver enzyme profiles, and histological protection of liver, kidney, and pancreatic tissues. Molecular docking confirmed strong binding of rutin and curcumin to key targets (α-glucosidase, α-amylase, and COX-2), supported by favorable ADMET properties and good safety profiles. Overall, the findings indicate that Pelargonium graveolens possesses multi-target therapeutic potential against diabetes and oxidative stress-related disorders.
CD
Keywords: Pelargonium graveolens; antidiabetic; antioxidant; molecular docking; rutin; curcumin.